Cultivation Practices and Knowledge of Local Rice Varieties among Benuaq Farmers in Muara Lawa District West Kutai, East Kalimantan-Indonesia - MEDI HENDRA; EDI GUHARDJA; DEDE SETIADI; EKO BAROTO WALUJO; YOHANES PURWANTO (Biodiversitas Journal of Biological Diversity, 2009)
This research aim to study how Benuaq society around Muara Lawa District, manage agriculture system and internal knowledge about rice varieties. This research use ethnobotanical approach: collecting ethnobotanical data of rice varieties and traditional system of swidden cultivation. Data was obtained by using direct participatory technique by interviewing the people (key informants) about their practice and perception. The interviews were unstructured open-ended discussion onknowledge and farming activities including about diversity in rice varieties. Subsequently, quantitative data from questionnaires was combined with depth-interview data from key informants. The Benuaq indigenous systems, practices, and cultivation preferences held by the Benuaq are guarded toward maintaining their rice diversity. The Benuaq systems of upland rice cultivation, site selection for umaq establishment, plant species for fertility indicator, and cultivation of wide ranges of upland rice varieties indicate their sophisticate knowledge in agriculture. Unfortunately there has been degradation in the indigenous knowledge among the young Benuaqs.Key words: Benuaq, ethnobotanical, indigenous, upland rice.